P38 initiates degeneration of midbrain GABAergic and glutamatergic neurons in diabetes models. (20th May 2022) - Farhadi, Aisan; Totonchi, Mehdi; Nabavi, Seyed Masood; Baharvand, Hossein; Pakdaman, Hossein; Hajizadeh‐Saffar, Ensiyeh; Mousavi, Seyed Ahmad; Hadi, Fatemeh; Al‐Sinawi, Hamed; Li, Quan; Zhang, Jin‐San; Tahamtani, Yaser; et al.
Abstract: Diabetes mellitus may cause tau protein hyperphosphorylation and neurodegeneration, but the exact mechanism by which diabetic conditions induce tau pathology remains unclear. Tau protein hyperphosphorylation is considered a major pathological hallmark of neurodegeneration and can be triggered by diabetes. Various tau‐directed kinases, including P38, can be activated upon diabetic stress and induce tau hyperphosphorylation. Despite extensive research efforts, the exact tau specie(s) and kinases driving neurodegeneration in diabetes mellitus have not been clearly elucidated. We herein employed different techniques to determine the exact molecular mechanism of tau pathology triggered by diabetes in in vivo and in vitro models. We showed that diabetes‐related stresses and glucose metabolism deficiency could induce cis P‐tau (an early driver of the tau pathology) accumulation in the midbrain and corpus callosum of the diabetic mice models and cells treated with 2‐deoxy‐D‐glucose, respectively. We found that the active phosphorylated level of P38 was increased in the treated cells and diabetic mice models. We observed that oxidative stress activated P38, which directly and indirectly drove tau pathology in the GABAergic and glutamatergic neurons of the midbrain of the diabetic mice after 96 h, which accumulated in the other neighboring brain areas after 2 months. Notably, P38 inhibition suppressed tau pathogenicity and risk‐taking behaviors in the animal models after 96 h. The data establish P38 as a central mediator of diabetes mellitus‐induced tau pathology. Our findings provide mechanistic insight into the consequences of this metabolic disorder on the nervous system. Abstract : Diabetes mellitus (DM) can induce oxidative stress and drive tau pathology in the midbrain and corpus callosum. Ci s P‐tau as an early driver of the tau pathology accumulated in the GABAergic and glutamatergic neurons. Inhibition of the P38 by daily injection of the SB203580 suppressed cis P‐tau formation and decreased phosphorylated P38 level in the TH/HY/MB of the diabetic mice.